Tissue structural phases of gut anastomosis formation by radiofrequent electric welding supply - S. S. Podpriatov; S. E. Podpryatov; S. G. Gichka; G. S. Marinsky; O. V. Chernets; V. A. Tkachenko; D. A. Grabovsky; K. G. Lopatkina; S. V. Tkachenko (Kazimierz Wielki University, 2017)
Introduction. The preferences of radiofrequency-based tissue fusion of intestinal anastomosis are based on its uncompleted healing and vital restructuration during the welding variant. But the radiofrequency fusion process monitoring still is sophisticated, so further researches are mandatory to create new settings. Aim. To study the phases of tissue changes that occurs in gut wall tissue during the welding anastomosis creating, as its estimating criteria. Material and methods. The same voltage, form and duration of the welding impulses' tissue effects, based on radio frequency 440 kHz were studied. The swine organ complex was delivered to laboratory during 6 hours at 4 оС, and then was heated to 28-32 оС into 0.9% NaCl. Two intestine walls having human sizes were positioned on electrodes inside the anastomotic device prototype. 120 experiments were provided using pressure values 2.1, 3.0, 3.9 and 5.0 N/mm2 for tissues thinning. After completion of the welding supply, anastomosed tissues were taken for morphological studies. Results. We established the 4 common phases of welding-provided tissue restructuration inside gut organ walls, starts from oedema and widening of connective tissue septums with slight collagen fibres denaturation, throw loosing of layers integrity with attaining wave-like periodical deformation, next to the start of two organ walls merging in local points into fissured tissue substrate, and the merging process spreads along the whole organ walls finally. Simultaneously, the formed tissues common substrate becomes solid structure, homogeneous density and coagulation depth. Conclusions. The structural phases of gut organs' tissues welding merging into homogeneous anastomosis substrate are: i) initial mucous epithelium destruction; ii) tissues loosening, partial fragmentation and orientation; iii) sealing of collagen fibres to smooth muscle cells; iv) derivation of walls merging points; v) forming continuous solid but structured tissue substrate, is dense and armoured by multi-point collagen fibres to smooth muscle cells sealing. Discussion. As for similarity of welding-provided restructuration phases, inside investigated gut organs, having so different walls, the welding anastomotic process could be uniform for surgical needs.